2008
DOI: 10.1002/chem.200800159
|View full text |Cite
|
Sign up to set email alerts
|

p‐Phenyleneethynylene Molecular Wires: Influence of Structure on Photoinduced Electron‐Transfer Properties

Abstract: A series of donor-acceptor arrays (exTTF-oPPE-C60) containing pi-conjugated oligo(phenyleneethynylene) wires (oPPE) of different length between pi-extended tetrathiafulvalene (exTTF) as electron donor and fullerene (C60) as electron acceptor has been prepared by following a convergent synthesis. The key reaction in these approaches is the bromo-iodo selectivity of the Hagihara-Sonogashira reaction and the deprotecting of acetylenes with different silyl groups to afford the corresponding donor-acceptor conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 80 publications
5
50
0
Order By: Relevance
“…[18] UV-Visible absorption studies on OPE wires terminated with dialkylamino donor and cyano, formyl or nitro acceptor groups showed a competition between the extension of the chromophores and a decrease of the ICT upon increasing the number of PE repeat units. [19] More extensive photophysical studies on series of extended-TTF-OPE-pyrrolidinoC 60 , [20,21] porphyrin-OPE-pyrrolidinoC 60 [22] and 3,5-dimethyl-4-(9-anthracenyl)julolidine-OPEnaphthalene-bis(dicarboximide) systems [23] gave  values of 0.20, 0.11 and 0.23 Å -1 , respectively. Other examples include boron dipyrromethene (BODIPY)-OPE systems.…”
Section: Extensive Studies Have Focused On Covalently-linked Donor-brmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] UV-Visible absorption studies on OPE wires terminated with dialkylamino donor and cyano, formyl or nitro acceptor groups showed a competition between the extension of the chromophores and a decrease of the ICT upon increasing the number of PE repeat units. [19] More extensive photophysical studies on series of extended-TTF-OPE-pyrrolidinoC 60 , [20,21] porphyrin-OPE-pyrrolidinoC 60 [22] and 3,5-dimethyl-4-(9-anthracenyl)julolidine-OPEnaphthalene-bis(dicarboximide) systems [23] gave  values of 0.20, 0.11 and 0.23 Å -1 , respectively. Other examples include boron dipyrromethene (BODIPY)-OPE systems.…”
Section: Extensive Studies Have Focused On Covalently-linked Donor-brmentioning
confidence: 99%
“…[21,23,38] The experimental data can be readily fitted to equation 1 giving an attenuation factor of = 0. [22] and = 0.20 Å -1 for extended-TTF-OPE-pyrrolidinoC 60 .…”
Section: Molecular Orbital Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher values of the attenuation factor revealed that the HOMO for this system is completely localized on the exTTF and does not reach into the bridge. The presence of triple bonds in exTTF-oPPE-C 60 disrupts the extended π-conjugation and influences in the charge transfer [79].…”
Section: Covalent Donor-bridge-acceptor Systemsmentioning
confidence: 99%
“…During the past few years, electron donor-acceptor (DA) dyads based on [60] fullerene, which upon photoexcitation give rise to photoinduced charge-separated states, have been the focus of intensive research as candidates for artificial photosynthetic reaction centers (5)(6)(7)(8)(9)(10). Remarkably, small reorganization energies (11) associated with the reduction of the C 60 cage lead to efficient photoinduced electron transfer occurring, with the generation of relatively long-lived charge-separated (CS) states.…”
Section: Introductionmentioning
confidence: 99%